EVALUASI KINERJA OPERASIONAL RIG SAAT PROSES WORK OVER DAN WELL SERVICE PADA SUMUR XT PT PERTAMINA CEPU FIELD DISTRIK 1 KAWENGAN - Tommy Daud Jeferson Talahatu; Erdila Indriani; Kristofol Waas (Journal Mechanical Engineering, 2025)
Workover and well service activities are routine activities to repair and maintain production wells, such as replacing oil pump equipment and changing well hole reservoir parameters such as drilling and cracking activities This is done to repair and maintain wells so that they can always produce according to the specified potential However, during the work, the production of each well that requires repair must be temporarily stopped until the well is repaired. The length of time a well is not producing depends on the length of the repair of the well. Therefore, drilling performance must be evaluated to avoid delays in well production in the long term. Based on the results of this study, the PDSI# 35.1/IDECO H-35-M rig has a performance level of 88% for 15 days; the performance presentation of the rig is good. In addition, from the results of the NPT using a Pareto diagram, there are several main problems that cause rig performance, namely, waiting for a bright day, waiting for equipment repair time, inspection/safety checklist, and waiting for licensing time.Keywords: Rig Operational Performance. Workover and Well service, Pareto Diagram, non-productive time